2013
DOI: 10.1121/1.4824450
|View full text |Cite
|
Sign up to set email alerts
|

Absolute pitch among students at the Shanghai Conservatory of Music: A large-scale direct-test study

Abstract: This paper reports a large-scale direct-test study of absolute pitch (AP) in students at the Shanghai Conservatory of Music. Overall note-naming scores were very high, with high scores correlating positively with early onset of musical training. Students who had begun training at age ≤5 yr scored 83% correct not allowing for semitone errors and 90% correct allowing for semitone errors. Performance levels were higher for white key pitches than for black key pitches. This effect was greater for orchestral perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Such individuals possess the rare ability called absolute (or perfect) pitch (AP), which is defined as the ability to identify the chroma (pitch class) of a tone or to produce a specific pitch without the aid of any reference tones (Levitin & Rogers, 2005;Zatorre, 2003;Takeuchi & Hulse, 1993;Baggaley, 1974). This rare ability occurs in less than 1% of the general population (Takeuchi & Hulse, 1993), whereby Asian people speaking tonal languages have a higher incidence rate of AP (Deutsch, Li, & Shen, 2013;Deutsch, Dooley, Henthorn, & Head, 2009;Deutsch, Henthorn, Marvin, & Xu, 2006;Deutsch, Henthorn, & Dolson, 2004a;Gregersen, Kowalsky, Kohn, & Marvin, 1999). Interestingly, whereas most of the AP possessors are musicians (Deutsch et al, 2009), a handful of them possess AP in terms of a savant skill in the context of autism (Brenton, Devries, Barton, Minnich, & Sokol, 2008;Heaton, Davis, & Happé, 2008) or Williams syndrome (Lenhoff, Perales, & Hickok, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such individuals possess the rare ability called absolute (or perfect) pitch (AP), which is defined as the ability to identify the chroma (pitch class) of a tone or to produce a specific pitch without the aid of any reference tones (Levitin & Rogers, 2005;Zatorre, 2003;Takeuchi & Hulse, 1993;Baggaley, 1974). This rare ability occurs in less than 1% of the general population (Takeuchi & Hulse, 1993), whereby Asian people speaking tonal languages have a higher incidence rate of AP (Deutsch, Li, & Shen, 2013;Deutsch, Dooley, Henthorn, & Head, 2009;Deutsch, Henthorn, Marvin, & Xu, 2006;Deutsch, Henthorn, & Dolson, 2004a;Gregersen, Kowalsky, Kohn, & Marvin, 1999). Interestingly, whereas most of the AP possessors are musicians (Deutsch et al, 2009), a handful of them possess AP in terms of a savant skill in the context of autism (Brenton, Devries, Barton, Minnich, & Sokol, 2008;Heaton, Davis, & Happé, 2008) or Williams syndrome (Lenhoff, Perales, & Hickok, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One strength of the present experiment is that AP performance was assessed with three separate tests. Two of these tests -the UCSF Test and the UCSD Test -have been externally administered in a number of previous studies 17, [27][28][29][30][31] , which makes their interpretation (i.e. in terms of AP thresholds) more straightforward.…”
Section: Comparisons With External Studiesmentioning
confidence: 99%
“…Finally, the third hypothesis considers the musical training regime and/or environment. For example, it has been shown that the prevalence of AP can be higher among musicians who speak tonal languages in comparison to non-tonal language speakers (Deutsch et al, 2006 , 2009 , 2013 ). In this case, the cognitive demand to extract meaning from similar sounds with varied intonations would extrapolate to other tasks, and therefore, contribute to pitch recognition and naming.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the cognitive demand to extract meaning from similar sounds with varied intonations would extrapolate to other tasks, and therefore, contribute to pitch recognition and naming. However, early music education policies in Asian countries may also contribute to the differences in the observed prevalence (Miyazaki and Ogawa, 2006 ; Miyazaki et al, 2012 ), as music education methods (i.e., “fixed-do” vs. “moveable-do”) and the type of instrument used in learning classes (Miyazaki et al, 2012 ; Deutsch et al, 2013 ). In this respect, at least to our knowledge, few studies have attempted to investigate the influence of music proficiency in the expression of AP, which may have been overlooked in previous reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation